EVALUATION OF MICROMECHANICAL PROPERTIES OF CARBON FIBER FABRIC USING NANOINDETATION - Pavel Klapálek; Zdeněk Prošek; Aleš Jíra; Lenka Melzerová (Acta Polytechnica CTU Proceedings)
This paper is focused mainly on nanoindentation of carbon fibers. Fibers are in form of carbon fiber fabric that is used in larger research that is focused on reinforcing beams made of glued laminated timber. Knowledge of this material on macro and micro level will help to understand its behavior in this specific type of use. Nanoindentation is method used in this paper to obtain material characteristics on micro level such as hardness and modulus of elasticity. Samples of the carbon fiber fabric had to be prepared for this specific testing method by polishing samples of carbon fabric attached in epoxy resin. In particular, it was found that the indentation hardness of the fibers ranges around 3.65 GPa and modulus of elasticity ranges around 26 GPa.